Unexpectedly high mutation rate of cyp11b1 compared to cyp21a2 in randomly-selected turkish women: a large screening study - Polat, S.; Karaburgu, S.; Unluhizarci, K.; Dundar, M.; Ozkul, Y.; Arslan, Y. K.; Karaca, Z.; Kelestimur, F. (Journal of endocrinological investigation, 2023)
Purpose Congenital adrenal hyperplasia (CAH) is a group of autosomal recessive disorders resulting from enzyme deficiencies associated with steroidogenesis. The clinical presentation of non-classic CAH (NCAH) in females is often indistinguishable from other hyperandrogenic disorders like polycystic ovary syndrome (PCOS). The data on the prevalence of NCAH in unselected women in the literature is scanty. The research aimed to evaluate the prevalence of NCAH, carrier frequencies, and the correlation between clinical symptoms and genotype in Turkish women. Methods The study group comprised two hundred and seventy randomly-selected unrelated asymptomatic women of reproductive age (18–45). Subjects were recruited from female blood donors. All volunteers underwent clinical examination and hormone measurements. The protein-encoding exons and exon–intron boundaries of the CYP21A2, CYP11B1, HSD3β2 and CYP21A2 promoter were sequenced by direct DNA sequencing. Results After genotyping, seven (2.2%) individuals were diagnosed with NCAH. The heterozygous carrier frequencies of CYP21A2, CYP21A2 promoter, CYP11B1, and HSD3β2 genes with 34, 34, 41, and 1 pathologic mutation were determined at 12.6%, 12.6%, 15.2%, and 0.37% of volunteers, respectively. Gene-conversion (GC) frequencies between CYP21A2/CYP21A1P and CYP11B1/CYP11B2 were determined as 10.4% and 14.8%, respectively. Conclusion Despite GC-derived higher mutation frequency determined in the CYP11B1 gene, the reason for the low frequency of NCAH due to 11OHD compared to 21OHD might be that gene-conversion arises with active CYP11B2 rather than an inactive pseudogene. HSD3β1 exhibits high homology with HSD3β2 located on the same chromosome; remarkably, it demonstrates low heterozygosity and no GC, most probably the outcome of a tissue-specific expression pattern.